If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 96 + -94y = 0 Solving 96 + -94y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-96' to each side of the equation. 96 + -96 + -94y = 0 + -96 Combine like terms: 96 + -96 = 0 0 + -94y = 0 + -96 -94y = 0 + -96 Combine like terms: 0 + -96 = -96 -94y = -96 Divide each side by '-94'. y = 1.021276596 Simplifying y = 1.021276596
| 14n+12=5n-6 | | 33-2(7r+9)=-9-6r | | D=w(1+Qn) | | 33-3(7r+9)=-9-6r | | x^3-7x^2+2x-14= | | 9x-y-3=0 | | 3a-15=42 | | -16m^2+25=0 | | f(6)=36+1.531 | | f(6)=36+.1531 | | 2n+6=17 | | y=sw-st^3 | | y=4-3*-5 | | y=-20+10 | | 14+-3p=-20 | | 9p^2=747 | | (x+2)(x-3)=(x+9)(x-4) | | 0=-16t+38.8+3 | | (x+10)= | | 69-3x=7x-19 | | y=-8+8 | | x^2-7=44 | | 4-5u+12+16u=6u-18 | | 5e^4x-6=13 | | 214-5x=40x+24 | | 5x+101=9x-7 | | 15a+15=75 | | 6x-2-8=0 | | 2t(t+2)=1 | | P=b+a | | 6x+2x+3=360 | | x^2-3=33 |